Membangun Branding Produk UMKM Melalui Media Sosial Tiktok - Lian Fawahan; Ita Marianingsih Purnasari (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The occurrence of the Covid-19 pandemic makes many MSMEs have to lose money and go out of business, whereas in Indonesia the most important joint that sustains the wheels of the country's economy is MSMEs. In addition to the pandemic, the challenge of MSMEs is rise of the digital economy movement is very rapid for making MSMEs demanded to understand information technology. The covid-19 pandemic is increasingly encouraging human activity through the internet network. One of the simplest steps to build a brand through TikTok social media. In 2020 number of downloads amounted to 63.3 million both in the Apple store and the play store the best-selling application is TikTok. Indonesia is the downloader of the application amounting to 11% of the total downloads of tiktok application, with tiktok MSME actors can build their product brand, considering it does not require a lot of cost and energy. The potential of the wider market and the future business will also be a consideration because tiktok social media is widely used by millennials who have high consumptive power. This study uses qualitative descriptive, uses literature studies quoted from book journals as well as relevant websites. The purpose of this study is to encourage MSMEs to have a good brand so that they can compete with other products, and through social media, especially TikTok, the MSME market segment can be wider internationally. Considering that social media has eliminated geography, meaning that when it can go viral social media, everyone can see MSME products. Keywords: MSMEs, Branding, TikTok